Adsorption of Cu(II) in aqueous solution by sodium dodecyl benzene sulfonate‐modified montmorillonite. Issue 4 (12th March 2023) - Wang, Danqi; Wang, Ruicong; Peng, Wencai; Wang, Yi; Zhang, Na; Duan, Yanan; Wang, Shiqin; Liu, Linye
Abstract: The pristine montmorillonite (P‐Mt) was modified with sodium dodecyl benzene sulfonate (SDBS) to form SDBS montmorillonite (SDBS‐Mt) for the purpose of enhancing the removal performance of Cu(II) from aqueous solution. The materials were characterized by means of XRD, SEM‐EDS, BET, and FTIR to analyze the surface morphology and structure. SDBS‐Mt displayed a higher adsorption capacity than P‐Mt. The adsorption kinetic model and the adsorption isotherm model are depicted by the pseudo‐second‐order kinetic equation and the Langmuir equation, respectively. The adsorption of Cu(II) on SDBS‐Mt is a spontaneous and endothermic process. The order of influence of coexisting cations on the adsorption of Cu(II) is Ni(II) > Co(II) > Zn(II). In addition, the adsorbent has great regeneration performance after five cycles of regeneration. The main mechanisms of Cu(II) adsorption by SDBS‐Mt may include electrostatic attraction, ion exchange, and complexation of sulfonate groups. In brief, SDBS‐Mt may be a promising, simple, and low‐cost adsorbent for the treatment of Cu(II) in aqueoussolutions. Abstract : The main mechanisms of Cu(II) adsorption by SDBS‐Mt may include electrostatic attraction, ion exchange, and complexation of sulfonate groups.